Improving an adult holding system for Mediterranean fruit fly, Ceratitis capitata, to enhance sterile male performance. (31st October 2011) - Silva, N.; Dantas, L.; Calisto, R.; Faria, M. J.; Pereira, R.
Abstract: The success of using the sterile insect technique (SIT) for Mediterranean fruit fly, Ceratitis capitata (Wiedemann), suppression programmes is dependent on the release into the field of sterile males that survive and compete successfully with wild males for matings with wild females. The effects of pre‐release aromatherapy using ginger root oil (GRO) and the addition of hydrolysed yeast (protein and other nutrients) to the fly diet, on sterile male dispersal, survival, sexual maturation and mating performance under laboratory and field conditions were evaluated. The interaction between providing protein and/or GRO treatment was also evaluated. Under field cage conditions, male mating performance was significantly higher in treatments with GRO but was unaffected by the provision of protein. There was no interaction between them. However, after releases under field conditions, survival of protein‐fed sterile males was significantly longer compared with protein‐deprived sterile males. The use of GRO should be incorporated into the sterile male–handling protocol for SIT programmes. In combination with the validation of the provision of these supplements, two new cage systems developed in the Madeira‐Med Programme were tested in comparison with the standard plastic adult rearing containers boxes for a more cost‐effective sterile male emergence, feeding, holding and collecting process at fly emergence and release facilities. This selected cages systems can handle approximately 1 million pupae and reduces manual labour and other costs while maintaining good sterile male quality.